2018
DOI: 10.1002/jts.22304
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Effect of Posttraumatic Stress Disorder Symptoms on Current Alcohol Use Through Negative Cognitions in Sexual Minority Men

Abstract: Self-medication theory posits that some trauma survivors use alcohol to cope with posttraumatic stress disorder (PTSD) symptoms, but the role of negative posttraumatic cognitions in this relationship is not well defined. We examined associations among PTSD symptoms, posttraumatic cognitions, and alcohol intoxication frequency in 290 men who have sex with men (MSM), who reported a history of childhood sexual abuse (CSA). Using a bootstrap approach, we examined the indirect effects of PTSD symptoms on alcohol in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
3
4
0
1
Order By: Relevance
“…The current findings thus broadly support the cognitive model of PTSD (Ehlers & Clark, 2000) and the self-medication hypothesis (see McCauley et al, 2012;Vujanovic et al, 2016), in which alcohol or drugs may function as a tool to avoid trauma-related negative cognitions and associated arousal and distress. Moreover, the findings build on previous evidence suggesting that negative cognitions about the self and others/the world may play an important role in the development, maintenance, and remission of posttraumatic sequelae (Dekel et al, 2013;Scher et al, 2017;Zhou et al, 2015) including substance use (Allwood et al, 2014;Banerjee et al, 2018;Blevins et al, 2016;Jayawickreme et al, 2012;Thompson & Kingree, 2010).…”
Section: Summary and Interpretationsupporting
confidence: 80%
“…The current findings thus broadly support the cognitive model of PTSD (Ehlers & Clark, 2000) and the self-medication hypothesis (see McCauley et al, 2012;Vujanovic et al, 2016), in which alcohol or drugs may function as a tool to avoid trauma-related negative cognitions and associated arousal and distress. Moreover, the findings build on previous evidence suggesting that negative cognitions about the self and others/the world may play an important role in the development, maintenance, and remission of posttraumatic sequelae (Dekel et al, 2013;Scher et al, 2017;Zhou et al, 2015) including substance use (Allwood et al, 2014;Banerjee et al, 2018;Blevins et al, 2016;Jayawickreme et al, 2012;Thompson & Kingree, 2010).…”
Section: Summary and Interpretationsupporting
confidence: 80%
“…There were small and significant correlations between scores on the PTCI-9 and two forms of behavioral dysregulation: disordered eating and alcohol use. Other studies have found a relationship between PTSD and disordered eating in veterans (Huston et al, 2019;Mitchell & Wolf, 2016) and a link between negative posttraumatic cognitions and alcohol use (Banerjee et al, 2018;Lyons et al, 2020). Disordered eating and alcohol use may serve as coping strategies for managing internal experiences associated with negative cognitions about the self, world, and self-blame (Engelberg et al, 2007;Khantzian, 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Snipes et al (2017) ont montré que les croyances post-traumatiques sur la sexualité et le pouvoir médiaient partiellement la relation entre le viol et les symptômes du TSPT chez les hommes. De plus, deux études ont exploré le rôle médiateur des cognitions post-traumatiques sur la relation entre le niveau de consommation d'alcool et les symptômes du TSPT (Blayney et al, 2016 ;Banerjee et al, 2018). Seule l'étude de Banerjee et al (2018) a révélé que les cognitions post-traumatiques médiaient la relation entre les symptômes du TSPT et la fréquence d'intoxication alcoolique (ß = 0,11).…”
Section: éTudes De Médiation (N = 9)unclassified